IEEE INFOCOM 2008 - The 27th Conference on Computer Communications 2008
DOI: 10.1109/infocom.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Turbo King: Framework for Large-Scale Internet Delay Measurements

Abstract: Abstract-Distance estimation and topological proximity in the. Besides deploying tracers and using virtual coordinates, distance is often estimated using end-to-end methods such as King [13] that rely on the existing DNS infrastructure. However, the question of accuracy in such end-to-end estimation and its ability to produce a large-scale map of Internet delays has never been examined. We undertake this task below and show that King suffers from non-negligible error when DNS zones employ geographically divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…showed that 32% of RDNS resolvers in their study use some sort of "hidden" forwarder [16]. A possible solution would be to move the RDNS in front of the NAT/PAT, but this may not be always possible or easy to do, depending on the specific network architecture or configuration (for example, a change in the network architecture may expose the RDNS to other kinds of attacks, beside cache poisoning).…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that 32% of RDNS resolvers in their study use some sort of "hidden" forwarder [16]. A possible solution would be to move the RDNS in front of the NAT/PAT, but this may not be always possible or easy to do, depending on the specific network architecture or configuration (for example, a change in the network architecture may expose the RDNS to other kinds of attacks, beside cache poisoning).…”
Section: Previous Workmentioning
confidence: 99%
“…In the following we will assume Γ T XID = 2 16 (perfect randomization of the TXID), and Γ port = 2 16 − 1024 (i.e., perfect randomization of all the ports excluding the first usually reserved 1024 ports). For the 0x20-bit encoding we consider three cases, namely Γ 0x20 = 2 6 for short domain names containing 6 letters (e.g., cnn.com, aol.com, etc.…”
Section: Robustness To Poisoning Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, others proposed techniques for monitoring networks and, possibly, reducing the amount of required measurements while keeping accurate the measured metrics [17,18,19,7,9]. In particular, Donnet et al [9] impose a limit on the number of traceroute monitor that can probe a given destination.…”
Section: Clustering Techniquesmentioning
confidence: 99%
“…Our third project studies the DNS infrastructure for Internet-wide delay measurements [8] and various botnet-related anomalies, which requires traversing the DNS tree with over 650M DNS requests. Sending such a large number of small packets presents a problem for Winsock and limits the duration of the measurement to days instead of minutes.…”
Section: Introductionmentioning
confidence: 99%